Proses Perundingan Bipartit sebagai Syarat Mutlak dalam Pemutusan Hubungan Kerja - Iwan; P.L Tobing (Syntax Corporation, 2023)
The Industrial Relations Court (PHI) is a sub-system of special courts placed within the general judicial sphere. PHI with absolute competence to adjudicate labor cases or disputes that occur at the pre-judicial level enters PHI, namely at the level of the tripartite process it turns out that it can also come into contact with the authority of the state administrative court, related to aspects of actions that must be taken by the state administrative agency in this case in the form of recommendations issued by mediators from the Manpower Office, Is the State Administrative Court authorized to Order the Manpower Office as a mediator? To issue a recommendation in a termination dispute? This research is a normative juridical research, with a historical approach, comparison and emphasis of research on secondary data which includes primary legal material, secondary legal material and tertiary legal material, with documentation methods and qualitative data analysis. The results of the study that the two-party negotiation process between employers and workers is a condition taken so that it can be forwarded to tripartite mediation. If the Manpower Office is not willing to mediate due to the non-fulfillment of the requirements in the form of bipartite evidence, in the event that one of the parties sues the PTUN based on the positive fictitious referred to in Article 53 of the Government Administration Law, the PTUN still cannot grant the request to order the Manpower Office to issue a Recommendation